Analisis Nilai Pendidikan Karakter Pada Buku Cerita Anak Domba yang Nakal Sebagai Bahan Bacaan Siswa Kelas III SDN 24 Woja - Kartika Astuti, Nofita; Siti Istiningsih; Lalu Wira Zain Amrullah (Mataram University, 2025)
Character education is an education that shapes an individual's personality. One of the efforts that can be done to instill the value of a child's character, one of which is by reading books. The purpose of this research is to describe the value of character education in the story book The Naughty Lamb. This book is published by PT Cahaya Pustaka Raga written by Renata Pohan. This research uses a qualitative descriptive research method with a research library approach or literature study. The data collection technique in this research uses a research library in the form of documentation analysis consisting of reading techniques, recording techniques, and classification techniques, then the data that has been collected is identified, analyzed, and described. The research location is at SDN 24 Woja, the primary data in this research is the storybook Anak Domba yang Nakal, and the secondary data in this research is the sources of written references (books, journals, research reports). The result of this research is the value of character education contained in the story book Anak Anak yang Nakal which is used as reading material for students in grade III SDN 24 Woja, including (1) Brave (2) Social Care (3) Honest (4) Friendly/Communicative (5) Democratic (6) Please Help (7) Love of Peace and (8) Mutual Forgive. Based on the value of character education that has been obtained, it is hoped that teachers will be more selective in choosing student reading books that support the learning process, as well as the use of the Naughty Lamb story book as student reading material is expected to provide an overview and understanding to students about good behaviors, and students can reap moral learning or character education values from the book.